Ibrutinib targets microRNA-21 in multiple myeloma cells by inhibiting NF-κB and STAT3 - Jing Ma; Wei Gong; Su Liu; Qian Li; Mengzheng Guo; Jinhan Wang; Suying Wang; Naiyao Chen; Yafei Wang; Qiang Liu; Hui Zhao (Tumor Biology)
The oncogenic microRNA-21 contributes to the pathogenesis of multiple myeloma. Ibrutinib (also referred to as PCI-32765), an inhibitor of Bruton’s tyrosine kinase, while its effects on multiple myeloma have not been well described. Here, we show that microRNA-21 is an oncogenic marker closely linked with progression of multiple myeloma. Moreover, ibrutinib attenuates microRNA-21 expression in multiple myeloma cells by inhibiting nuclear factor-κB and signal transducer and activator of transcription 3 signaling pathways. Taken together, our results suggest that ibrutinib is a promising potential treatment for multiple myeloma. Further investigation of mechanisms of ibrutinib function in multiple myeloma will be necessary to evaluate its use as a novel multiple myeloma treatment.